IMPLEMENTASI METODE CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSA PENYAKIT TELINGA HIDUNG TENGGOROKAN (THT) BERBASIS WEB - Sihotang, Mario; Setyaningrum, Putri Taqwa (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
Ear Nose Throat Disease (ENT) is a disease that affects many Indonesian people. Beji Mulyo Village is a village in the Tungkal Jaya sub-district, Banyuasin district, Palembang City. This village only has a health center and a midwife as the head of health in the village. The problem experienced by Beji Mulyo Village is the lack of experts to treat ENT diseases. Besides that, to find an ENT specialist, the community has to travel quite a distance to find a hospital in the city. Therefore it is necessary to implement an expert system with the certainty factor method with the aim of being able to help and facilitate the community in providing diagnostic information related to diseases and initial treatment to detect diseases that can be given to people affected by ear disease. The results of testing the system from 20 patient data with the application of the certainty factor method obtained an accuracy rate above 98%.